Musculoskeletal Screening Tests and Bony Hip Morphology Cannot Identify Male Professional Soccer Players at Risk of Groin Injuries: A 2-Year Prospective Cohort Study. Issue 6 (May 2018) - Mosler, Andrea B.; Weir, Adam; Serner, Andreas; Agricola, Rintje; Eirale, Cristiano; Farooq, Abdulaziz; Bakken, Arnhild; Thorborg, Kristian; Whiteley, Rod J.; Hölmich, Per; Bahr, Roald; Crossley, Kay M.
Background: Musculoskeletal hip/groin screening tests are commonly performed to detect at-risk individuals. Bony hip morphology is considered a potential intrinsic risk factor but has not been examined prospectively. Purpose: To evaluate the association between intrinsic risk factors identified from musculoskeletal and radiographic screening tests and hip/groin injuries leading to time loss from training and/or match play in professional male soccer players. Study Design: Prospective cohort study; Level of evidence, 2. Methods: Male professional soccer players, aged ≥18 years, underwent screening specific for hip/groin pain during 2 consecutive seasons of the Qatar Stars League. The screening battery included pain provocation, range of motion, and strength tests as well as a hip radiographic examination. The radiographic examination included an anteroposterior pelvic view and 45° Dunn view, with bony hip morphology determined using quantitative methods. Time-loss (≥1 day) hip/groin injuries and individual player exposure (training and match play) were recorded prospectively, and injuries were categorized as adductor-related, inguinal-related, iliopsoas-related, pubic-related, or hip-related groin pain, or "other, " as recommended in the Doha agreement. We calculated hazard ratios (HRs) from univariate and multivariate Cox regression models to assess the relationship between potential risk factors and hip/groin injuries. Results: There were 438 players, completing 609 player seasons, and 113 hip/groin injuries that met the criteria for inclusion, with 85 injuries categorized as adductor-related. The proportion of players with bony morphological variants was the following: cam, 71%; pincer, 5%; and acetabular dysplasia, 13%. Previous hip/groin injuries (HR, 1.8; 95% CI, 1.2-2.7) and eccentric adduction strength were associated with the risk of hip/groin injuries. Higher (>1 SD above the mean) than normal eccentric adduction strength was associated with an increased risk for all hip/groin injuries (HR, 1.6; 95% CI, 1.0-2.5). Lower (<1 SD below the mean) than normal eccentric adduction strength was associated with an increased risk for adductor-related injuries (HR, 1.7; 95% CI, 1.0-3.0). No other musculoskeletal screening test or bony hip morphology variables were associated with the injury risk. Conclusion: Previous groin injuries and eccentric adduction strength were associated with the risk of groin injuries. However, these associations were not strong enough to identify an "at-risk" individual, and therefore, musculoskeletal screening tests were not useful to dictate individualized prevention strategies. Bony hip morphology was not associated with the risk of groin injuries.